Heat stress induced piRNA alterations in pachytene spermatocytes and round spermatids - Poonam Mehta; Shruti Sethi; Santosh Kumar Yadav; Gopal Gupta; Rajender Singh (BMC, 2024)
Abstract Background Spermatogenesis is a temperature-sensitive process, and elevation in temperature hampers this process quickly and significantly. We studied the molecular effects of testicular heating on piRNAs and gene expression in rat testicular germ cells. Methods We generated a cryptorchid rat model by displacing the testis from the scrotal sac (34 °C) to the abdominal area (37 °C) and sacrificed animals after 1 day, 3 days, and 5 days. Pachytene spermatocytes and round spermatids were purified using elutriation centrifugation and percoll gradient methods. We performed transcriptome sequencing in pachytene spermatocytes and round spermatids to identify differentially expressed piRNAs and their probable targets, i.e., TE transcripts and mRNAs. Results As a result of heat stress, we observed significant upregulation of piRNAs and TE transcripts in testicular germ cells. In addition to this, piRNA biogenesis machinery and heat shock proteins (Hsp70 and Hsp90 family members) were upregulated. mRNAs have also been proposed as targets for piRNAs; therefore, we shortlisted certain piRNA-mRNA pairs with an inverse relationship of expression. We observed that in testicular heat stress, the heat shock proteins go hand-in-hand with the upregulation of piRNA biogenesis machinery. The dysregulation of piRNAs in heat-stressed germ cells, increased ping-pong activity, and disturbed expression of piRNA target transcripts suggest a connection between piRNAs, mRNAs, and TE transcripts. Conclusions In heat stress, piRNAs, piRNA machinery, and heat shock proteins are activated to deal with low levels of stress, which is followed by a rescue approach in prolonged stressaccompained by high TE activity to allow genetic mutations, perhaps for survival and adaptability.